1999
DOI: 10.1002/(sici)1096-9098(199908)71:4<220::aid-jso3>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic carcinomas of the breast

Abstract: Background and Objectives: Metaplastic carcinomas of the breast are rare neoplasms. The purpose of the present study is to better characterize the clinical course, treatment, and prognostic factors of metaplastic breast carcinomas. Methods: Data of 14 patients with metaplastic breast carcinoma were retrospectively reviewed. The follow-up period ranged from 2 months to 10 years, 10 months (median 4.3 years). Results: The patients' ages ranged from 38 to 66 years (median 50.5 years). The tumors were 2.5 to 18 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
1
9

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 14 publications
(52 reference statements)
9
75
1
9
Order By: Relevance
“…The absence of hormone receptor expression on tumors restricts the application of hormonal therapy. Chao et al (12) reported no survival advantage of post-operative radiotherapy and various neoadjuvant chemotherapy regimens; however, different and/or mixed chemotherapy regimens and dose schedules may be more effective. Therefore, traditional surgery is the preferred treatment choice (2).…”
Section: Pathological Type Of Carcinoma Sonography ------------------mentioning
confidence: 99%
“…The absence of hormone receptor expression on tumors restricts the application of hormonal therapy. Chao et al (12) reported no survival advantage of post-operative radiotherapy and various neoadjuvant chemotherapy regimens; however, different and/or mixed chemotherapy regimens and dose schedules may be more effective. Therefore, traditional surgery is the preferred treatment choice (2).…”
Section: Pathological Type Of Carcinoma Sonography ------------------mentioning
confidence: 99%
“…Due to a rapidly growing and palpable large mass (≥ 5 cm) in MBC patients, MRM was the main surgical procedure in most series (Pitts et al, 1991;Gutman et al, 1995;Chao et al, 1999;Rayson et al, 1999;Al Sayed et al, 2006;Pezzi et al, 2007). However, BCS could not be precluded for appropriate MBC patients who had absolute or relative indications.…”
Section: Surgical Therapymentioning
confidence: 99%
“…Al Sayed et al reported that adjuvant chemotherapy was administered to nine patients and two of them experienced distant relapse upon first disease recurrence, and the 3-year OS for these patients were worse than those who did not receive adjuvant systemic therapy, however the difference was not statistically significant (Al Sayed et al, 2006). Chao et al found that 5 cases received adjuvant chemotherapy had a poorer OS than the patients who never take in chemotherapy (Chao et al, 1999). In the retrospective study by Bae et al, the 3-year DFS was worse than triple negative breast carcinoma for the lymphatic metastases (Bae et al, 2011).…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with MBC were most commonly found to be older, with tumors of larger size and more advanced stage; they usually tested negative for ER and the tumors were poorly differentiated (11). Clinical examination usually reveals fast-growing palpable tumors (10,12). Most patients present with a well-defined mass over 2 cm in size, sometimes reaching 4-5 cm (3,10,13).…”
Section: Discussionmentioning
confidence: 99%